Choice of Technology in Low-Wage Countries: A Nonneoclassical Approach - Lecraw, Donald J. (Quarterly Journal of Economics, 1979)
Journal Article Choice of Technology in Low-Wage Countries: A Nonneoclassical Approach Get access Donald J. Lecraw Donald J. Lecraw University of Western Ontario Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 93, Issue 4, November 1979, Pages 631–654, https://doi.org/10.2307/1884473 Published: 01 November 1979